Surgical Resection of Gastro-Pleural-Bronchial Fistula after Prolonged Endoscopic Treatments. Issue 3 (March 2022) - Nelson, Cannon; Suijka, Joseph; DuCoin, Christopher
Sleeve gastrectomy is the most commonly performed bariatric surgery in the United States. While complication rates are typically low, some studies have reported leaks in up to 2.4-5.3% of cases. Here, we examine such a case with subsequent failure of numerous endoscopic interventions ultimately necessitating formal resection of a gastro-Pleural-bronchial fistula.